Sliding Mode Control of An X4-AUV - Zainah, Md. Zain; N. N. A., Hanipah; Maziyah, Mat Noh; N., Harun; K. A. A., Rahim; N. M., Zain (2015)
This paper presents a design method for attitude control of an autonomous underwater vehicle(X4-AUV) based sliding mode control. We are interested in the dynamic modeling of X4-AUV because of it complexity. The dynamic model is used to design a stable and accurate controller to perform the best tracking and attitude results. To stabilize the overall systems, each sliding mode controller is designed based on the Lyapunov stability theory. The advantage of sliding mode control is it’s not being sensitive to model errors, parametric uncertainties and other disturbances. Lastly, we show that the control law has a good robust and good stability through simulation.